The wizard of Oz. - Garland, Judy.; Fleming, Victor, 1883-1949.; LeRoy, Mervyn, 1900-1987. (Burbank, CA : Metro-Goldwyn-Mayer. ; production company.; Warner Home Video (Firm), 2013)
The charming film based on the popular L. Frank Baum novel, Dorothy and her dog Toto, are caught in a tornado's path and somehow end up in the land of Oz. Here she encounters some memorable friends and foes in her journey to meet the Wizard of Oz who everyone says can help her return home and possibly grant her new friends their goals of a brain, heart and courage.
Originally produced as a motion picture in 1939.
Keywords: Musical films; Fantasy films; Children's films